Enhancement of pool boiling heat transfer in water on aluminum surface with high temperature conductive microporous coating. (April 2019) - Godinez, Juan C.; Fadda, Dani; Lee, Jungho; You, Seung M.
Highlights: Study of the effects of an aluminum high temperature conductive microporous coating on pool boiling. Aluminum microporous coating (Al-HTCMC) fabricated using different aluminum powder particle sizes. Coating thickness optimized to yield highest nucleate boiling heat transfer coefficients. Boehmite treatment applied to aluminum surface with the microporous coating. Abstract: The effects of an aluminum high temperature conductive microporous coating (Al-HTCMC) on the nucleate boiling heat transfer (NBHT) coefficient and critical heat flux (CHF) are studied in saturated distilled water at 1 atm. Aluminum powders with three different mean particle diameters (dm = 11, 24, and 66 µm) are used in the fabrication of the Al-HTCMC. For each mean particle diameter, an optimal coating thickness to yield the highest NBHT coefficient is determined. The optimized Al-HTCMC thickness is found to result in comparable NBHT coefficients regardless of the particle diameter. Pool boiling tests with a plain aluminum surface are used for comparison. The coated and plain aluminum surfaces are treated equally before the pool boiling tests to establish a Boehmite oxidation nano layer on the aluminum surfaces. Following the Boehmite treatment, the contact angle is unmeasurable (∼0°) with the Al-HTCMC surface and 12° with a plain aluminum surface. Then, pool boiling tests are performed and reveal comparable CHF (1725–1850 kW/m 2 ) values with or without the Al-HTCMC. However, the Al-HTCMC is shown experimentally to improve the NBHT coefficient by a factor of five as the wall superheat is reduced by from 31 K to 6 K just before CHF. The results obtained are also compared to similar work using an HTCMC layer on a copper surface to demonstrate the performance of the Al-HTCMC.